The Effect of Cream and Gel Vehicles on the Percutaneous Absorption and Skin Retention of a New Eugenol Derivative With Antioxidant Activity - Makuch, Edyta; Nowak, Anna; Günther, Andrzej; Pełech, Robert; Kucharski, Łukasz; Duchnik, Wiktoria; Klimowicz, Adam (Frontiers in Pharmacology, 2021)
The effect of cream and gel vehicles containing clove water on skin permeability was compared for a new eugenol derivative (eugenyl dichloroacetate — EDChA) with antioxidant activity. In vitro permeation experiments were conducted in a Franz cell with porcine skin. The cumulative mass and skin accumulation of EDChA were investigated and compared. The antioxidative capacity of the studied vehicles was determined by using the diphenylpicrylhydrazyl (DPPH) free radical reduction method. The antioxidant activity (evaluated with DPPH, ABTS, and the Folin–Ciocalteu methods) of the fluid that penetrated through the pig skin and of the fluid obtained after the skin extraction, were also determined. For comparison, eugenol was also tested. The results of this work could contribute to the development of vehicles with antioxidant potential estimated after 24 hours of conducting the experiment, which indicates long-term protection against reactive oxygen species (ROS) in the deeper layers of the skin. The waste water from the clove buds steam distillation - contains several valuable biologically active compounds, and its use is environmentally friendly. We observed that gel vehicles were the best enhancer of skin permeation for both eugenol and its derivative. In most cases, - similar cumulative masses of eugenol and its ester were found in the acceptor fluid. The accumulation of EDChA was higher for cream vehicles in relation to the parent eugenol when applied onto the skin. The greatest amounts of eugenol were accumulated in the skin when these compounds were used in gel vehicles.